Cytotoxic and genotoxic effects of (R)‐ and (S)‐ricinoleic acid derivatives. Issue 7 (6th April 2020) - Blaszczyk, Alina; Matysiak, Sylwia; Kula, Jozef; Szostakiewicz, Katarzyna; Karkusiewicz, Zaneta
Abstract: ( R )‐ricinoleic acid is the main component of castor oil from Ricinus communis L. Due to the presence of the hydroxyl group in homoallylic position and asymmetrically substituted carbon atom, it may undergo a number of chemical and biochemical transformations resulting in the products with some specific bioactivities. Conversion of ( R )‐ricinoleic acid into its ( S )‐enantiomer enables synthesis of both ( R )‐ and ( S )‐ricinoleic acid derivatives and comparison of their biological activities. In the present research, ( R )‐ and ( S )‐ricinoleic acid amides synthesized from methyl ricinoleates and ethanolamine or pyrrolidine as well as acetate derivatives of ethanolamine amides were studied to demonstrate their biological activities using HT29 cancer cells. Double staining of cells with fluorochromes (Hoechst 33258/propidium iodide) as well as 2, ′7′‐dichlorodihydrofluorescein (DCF) and comet assays were performed. Both the tested amides and acetates caused DNA damage and induced apoptotic and necrotic cell death. In the case of ( R )‐ and ( S )‐enantiomers of one of the tested acetates, significant difference in the ability to induce DNA damage was observed, which showed the impact of the stereogenic center on the activities of these compounds. Abstract : Different derivatives of ricinoleic acid are known to have important biological activities. We investigated biological effects of ricinoleic acid amides synthesized from methyl ricinoleates and ethanolamine or pyrrolidine as well as acetate derivatives of ethanolamine amides in cancer HT29 cells. Both the tested amides and acetates caused DNA damage and induced apoptotic and necrotic cell death. A clear difference between activity of ( R )‐ and ( S )‐enantiomers of the tested compounds was observed in the case of one acetate derivative.